Antenatal survey of women’s birthing choices in Qatar - Suruchi Mohan (14568689) (2020)
Objectives Attitudes towards labour care and women’s choices for their preferred mode of delivery are documented in studies from the around the world, however less is known about women’s birth choices in the Middle East. This study was designed with the aim of exploring beliefs and attitudes in this region. Methods Voluntary participation in an ethics-approved survey was offered to pregnant women attending the antenatal clinic at Sidra Medicine from August 2018 to January 2019 with no exclusion criteria. Results Of the 346 respondents, 58.1% were Arabic and the remainder expatriates. This group composition allowed comparison between women native and non-native to the Gulf region. Arabic and non-Arabic women differed significantly in previous birth experiences: the Arabs had had more doctor-led deliveries (45 vs. 34%), epidurals (56.6 vs. 45%) and episiotomies (65.7 vs. 54%). 70.2% of the respondents chose a normal delivery as their preferred birth mode though a smaller majority of the Arabic subgroup did (63.2 %). 60.4% preferred delivery by doctors and longer hospital stays (47.6), more so Arabic participants (64.7 and 68.6 %). Significantly less Arabs, would choose husbands as birth partners (51.2 vs. 86.2%) and more expressed a gender preference for doctors. Other group choices are presented. Conclusions Though women in this region made comparable choices about mode of delivery as their Western counterparts, they demonstrated an expectation of a culturally distinct and more medicalized approach to care in labour. The findings highlight the need for further studies to inform regional obstetric care and health education interventions as well as tailoring maternity care services. Other information  Published in: Journal of Perinatal Medicine License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1515/jpm-2020-0148